Pengaruh Realistic Mathematics Education Berbantuan Media Augmented Reality Terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Mesa Aprilia Anisman; Amir Luthfi; Molli Wahyuni; Astuti Astuti; Zulfah Zulfah (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study was motivated by the low level of students' mathematical concept comprehension. The objective of this study was to determine the effect of the Realistic Mathematics Education (RME) model assisted by Augmented Reality (AR) media on students' mathematical concept comprehension. This study employed a quantitative quasi-experimental method with a Non-Equivalent Control Group Design. The population consisted of all seventh-grade students at SMP Negeri 3 XIII Koto Kampar for the 2024/2025 academic year, with class VII B as the experimental class (RME-AR treatment) and class VII A as the control class (Expository Model). Data were collected through observation, tests, and documentation. The results indicated a significant effect of the AR-assisted RME model on students' mathematical concept comprehension (Sig. = 0.000 < 0.05). The average post-test score of the experimental group (76.87) was higher than that of the control group (64.29). Furthermore, the N-Gain test showed that the experimental group achieved an improvement of 71.13% (moderately effective), while the control group only achieved 55.38% (less effective). These findings demonstrate that the RME model assisted by AR media has a significant effect and is more effective in enhancing students' mathematical concept comprehension compared to expository learning.